An in vitro ADME and in vivo Pharmacokinetic Study of Novel TB-Active Decoquinate Derivatives - Tanner, Lloyd; Haynes, Richard K.; Wiesner, Lubbe (Frontiers in Pharmacology, 2019)
Tuberculosis (TB) is currently the leading cause of mortality due to an infectious disease, despite the existence of multiple effective first-line and second-line drugs. The current anti-TB regimen requires a prolonged treatment period of around 6 months and is only efficacious against drug-sensitive strains of Mycobacterium tuberculosis (Mtb). With a rise in cases of multi-drug resistant and extensively drug resistant strains of Mtb, newer treatments comprising compounds with novel mechanisms of action are required. Although decoquinate (DQ) is inactive against Mtb, its derivatives are of interest to anti-TB drug discovery because of their potential to permeate the mycobacterial cell wall, Mtb-infected macrophages, and granulomatous lesions by passive diffusion. The compounds also display mechanisms of action which are unlike those of currently used quinolones, potentially displaying activity against new targets. Three such derivatives bearing an alkyl group at N-1 and an amide group at C-3 (RMB 041, -043, and -073) displayed potent in vitro activities against Mtb H37Rv (90% minimum inhibitory concentrations, MIC90 = 1.61, 4.18, and 1.88 μM, respectively) and high selectivity indices (10-25). In this study, we evaluated the drug-like properties (in vitro microsomal stability, microsomal/plasma protein binding, kinetic solubility, lipophilicity, and passive permeability) and pharmacokinetic parameters of these compounds after intravenous and oral administration to male C57BL/6 mice. The compounds showed markedly improved kinetic solubilities compared to that of the parental DQ and were metabolically stable in vitro. The maximum concentrations reached after oral administration were 5.4 ± 0.40, 5.6 ± 1.40, and 2.0 ± 0.03 μM; elimination half-lives were 23.4 ± 2.50, 6.2 ± 0.80, and 11.6 ± 1.30 h; and bioavailabilities were 21.4 ± 1.0, 22.1 ± 2.2, and 5.9 ± 1.3 for RMB041, -043, and -073, respectively. These compounds therefore display promising drug-like properties, and their pharmacokinetic/toxicity profiles (including long half-lives both in vitro and in vivo) support their potential as candidates for further investigation in animal models of Mtb infection.